MENGEMBALIKAN PILKADA LANGSUNG MELALUI DPRD: WACANA USANG KETATANEGARAAN YANG TAK PERNAH USAI - Helen, Zennis; Mulyawan, Fitra (Ensiklopedia of Journal, 2025)
Abstract: Direct regional head election certainly has advantages and disadvantages because no system is perfect. The advantage of the direct election system is that it strengthens political decentralization in the regions, the people in the regions become stronger because the elected regional heads will side with the people and know the needs and urgency in the regions and the people choose directly who will lead them. It is certain that what the people choose is a leader who is in accordance with their conscience. And the direct regional head election system also has shortcomings such as high political costs and massive money politics. But that is not a reason to return him for election to the DPRD. However, by improving the regional elections so that direct regional elections remain consistent. Keywords: Pilkada, DPRD, State Administration.